A method for separating lanthanide elements in a beryllium salt system
Through constant potential electrolysis and co-deposition technology in beryllium salt system, the problem of lanthanide cannot be separated directly is solved, efficient separation of lanthanides and online processing of molten salt reactor fuel is achieved, and the neutron economy of the reactor is improved sex.
Patent Information
- Application Number
- CN202410456383.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-04-16
AI Technical Summary
In the prior art, the lanthanides cannot be separated directly in the beryllium salt system, resulting in low fuel treatment efficiency of molten salt stacks and poor neutron economy.
By performing constant potential electrolysis in the beryllide salt system, co-deposition of co-deposition ions with lanthanides is used to form inter-lanthanide-decreased intermetallic compounds, thereby achieving separation of lanthanides.
The direct and effective separation of lanthanides in the beryllium salt system is achieved, the online processing efficiency of molten salt reactor fuel is improved, and the neutron economy of the reactor is enhanced.
Smart Images

Figure CN118531451B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for separating lanthanides in a beryllium salt system. Background Technology
[0002] Beryllium salts, including BeF2 and LiF or NaF, serve as fuel carriers and heat transfer media in molten salt reactor (MSR) systems. Nuclear fuel, in the form of fluorides (such as UF4 and ThF4), dissolves in beryllium salts and undergoes fission reactions in the reactor core, releasing heat and generating various fission products. These include gaseous fission products with large neutron absorption cross-sections (such as Kr, Xe, and T) and soluble lanthanide fission products (mainly including La, Ce, Pr, Nd, Sm, Eu, and Gd). The accumulation of soluble lanthanide fission products within the reactor consumes valuable neutron resources necessary to sustain the fuel chain reaction in the reactor core, significantly reducing the reactor's neutron economy. Therefore, periodic or in-situ separation of lanthanide fission products is essential. The separation of lanthanide fission products is one of the core issues in molten salt reactor fuel reprocessing.
[0003] Given the significant challenges of directly separating lanthanide fission products online, researchers have proposed the concept of batch processing, drawing inspiration from traditional reactor fuel reprocessing methods. Batch processing can be understood as a fuel reprocessing model, a compromise or alternative approach. This method utilizes various separation technologies to separate and recover valuable and easily separable components from the fuel salt, which are then resynthesized and returned to the molten salt reactor. Currently, research has focused on fluorination volatilization or electrolytic recovery technologies for uranium recovery, vacuum distillation and liquid metal reduction extraction technologies for carrier salt recovery, and electrochemical separation technologies for thorium recovery. While the fuel reprocessing model can theoretically support the successful operation of molten salt reactors, the cost of fuel processing is high, and it fails to fully leverage the advantages of online fuel processing in molten salt reactors, thus serving only as a transitional measure. To fully realize the inherent advantages of molten salt reactors, reliance will inevitably be placed on online separation technologies, including those for lanthanide fission products. Summary of the Invention
[0004] To overcome the technical deficiency of existing technologies that cannot directly separate lanthanides from beryllium salt systems, this invention provides a method for separating lanthanides from beryllium salt systems. The method described in this invention can directly and effectively separate lanthanide fission products from beryllium salt systems and can be used for online processing of molten salt reactor fuel.
[0005] This invention provides a method for separating lanthanides in a beryllium salt system, comprising the following steps: electrolyzing a beryllium salt system containing lanthanides and co-deposited ions at a constant potential;
[0006] The beryllium salt system includes beryllium fluoride salts;
[0007] The co-deposited ions include one or more of Zn(II), Al(III), Ga(III), Ge(IV), Si(IV), Pb(II), Sn(II), In(II), Mn(II), Ni(II), Fe(II), Cu(II), Cd(II), and Co(II).
[0008] In this invention, the beryllium fluoride salt is preferably one or more of FLiBe, FNaBe, and BeF2.
[0009] In this invention, the beryllium salt system may also include other fluoride salts besides the beryllium fluoride salt, such as one or more of LiF, NaF, UF4, ThF4 and ZrF4.
[0010] In this invention, the beryllium salt system may also include lithium fluoride beryllium molten salt, such as 67LiF-33BeF2.
[0011] In this invention, the beryllium salt system may further include sodium fluoride beryllium molten salt, such as 57NaF-43BeF2.
[0012] In a specific embodiment of the present invention, the beryllium salt system includes BeF2 and LiF, for example, 67LiF-33BeF2. Wherein, 67LiF-33BeF2 refers to a molar ratio of LiF to BeF2 of 67:33.
[0013] In a specific embodiment of the present invention, the beryllium salt system includes BeF2 and NaF, for example, 57NaF-43BeF2. Wherein, 57NaF-43BeF2 refers to a molar ratio of NaF to BeF2 of 57:43.
[0014] In a specific embodiment of the present invention, the beryllium salt system includes LiF, BeF2 and UF4.
[0015] In a specific embodiment of the present invention, the beryllium salt system includes LiF, BeF2 and ThF4.
[0016] In a specific embodiment of the present invention, the beryllium salt system includes LiF, BeF2, UF4, and ThF4.
[0017] In a specific embodiment of the present invention, the beryllium salt system includes LiF, BeF2, UF4, ThF4 and ZrF4.
[0018] In this invention, the lanthanide elements are generally one or more of Pr, Nd, Gd, Ce, La, Sm and Eu.
[0019] In this invention, the lanthanides are preferably present in the form of lanthanide fluorides.
[0020] The lanthanide fluoride may be one or more of PrF3, NdF3, GdF3, CeF3, LaF3, SmF3 and EuF3.
[0021] In this invention, the lanthanide elements are generally derived from lanthanide fission products.
[0022] In this invention, the beryllium salt system is typically heated and melted before constant potential electrolysis.
[0023] Preferably, the heating and melting temperature is 500-800℃.
[0024] Preferably, the heating and melting are carried out in an inert gas atmosphere, such as argon or helium.
[0025] In this invention, the constant potential electrolysis method can be a conventional constant potential electrolysis method in the art. Preferably, a three-electrode system is used for the constant potential electrolysis, the three-electrode system including a working electrode, an auxiliary electrode, and a reference electrode. The reference electrode serves as the reference electrode for the working electrode and the auxiliary electrode, and the working electrode and the auxiliary electrode form a conductive circuit.
[0026] In this invention, preferably, the atmosphere in which the constant potential electrolysis is performed is an inert gas atmosphere, such as argon or helium. The function of the inert atmosphere is to ensure that the three electrodes and their accessories are not oxidized at high temperatures and to prevent the beryllium salt system from being contaminated.
[0027] In this invention, the working electrode can be made of Ni, Cu, Cu-Zn alloy, Mo, Pd, Ir, Pt or C material, and Cu-Zn alloy is also known as brass.
[0028] In this invention, the working electrode generally includes electrode material and auxiliary material, wherein the auxiliary material generally includes a sleeve, etc.
[0029] In this invention, preferably, the purity of the electrode material of the working electrode is not less than 95%.
[0030] In this invention, the auxiliary electrode may be graphite, glassy carbon, Pt, Mo, or Ni.
[0031] In this invention, the auxiliary electrode generally includes an electrode material and an auxiliary material, wherein the auxiliary material generally includes a sleeve, etc.
[0032] In this invention, preferably, the purity of the electrode material of the auxiliary electrode is not less than 95%.
[0033] In this invention, the reference electrode is preferably a beryllium electrode. The beryllium electrode may comprise a beryllium metal rod and a LiF-BeF2 molten salt. As is known to those skilled in the art, in the beryllium electrode, a beryllium metal rod is used as the electrode material, and a portion of the beryllium metal rod is immersed in the LiF-BeF2 molten salt.
[0034] The molar ratio of LiF to BeF2 in the LiF-BeF2 molten salt is preferably 1:1 to 4:1, for example, 2:1.
[0035] The diameter of the beryllium metal rod can be 2 to 3 mm.
[0036] As is known to those skilled in the art, the beryllium electrode generally also includes a sleeve. The ratio of the total volume of the LiF-BeF2 molten salt to the volume of the sleeve is preferably 0.3 to 0.5. The wall thickness of the sleeve is preferably 1 to 5 mm. The sleeve can be made of an inert material resistant to molten salt corrosion, preferably a ceramic material, such as hot-pressed boron nitride, alumina, magnesium oxide, or zirconium oxide. The inert material refers to a material with very stable chemical properties that does not easily react chemically with other substances. The thinnest part of the sleeve at its bottom is preferably 0.1 to 1.0 mm thick.
[0037] In this invention, the reference electrode generally includes electrode material and auxiliary material, wherein the auxiliary material generally includes a sleeve, etc.
[0038] In this invention, preferably, the purity of the electrode material of the reference electrode is not less than 95%.
[0039] In this invention, the power source for constant potential electrolysis can be a constant potential electrolysis power source or a constant potential meter with a potential control function.
[0040] In this invention, the constant potential electrolysis can be performed under the control of an electrochemical workstation. The electrochemical workstation is preferably a Kosteel electrochemical workstation, such as the CS350M Kosteel electrochemical workstation.
[0041] In this invention, the constant potential of the constant potential electrolysis is generally the potential value of the working electrode relative to the reference electrode.
[0042] In this invention, preferably, the constant potential of the constant potential electrolysis is 0.18 to 0.55V, more preferably 0.3V to 0.5V.
[0043] In this invention, the constant potential electrolysis causes the lanthanide elements and the co-deposited ions to co-deposit on the working electrode, forming a lanthanide-poor intermetallic compound. In this lanthanide-poor intermetallic compound, the molar percentage of the lanthanide elements is lower than the molar percentage of other metal elements. For example, LaNi5 is a lanthanide-poor intermetallic compound, while LaNi or La2Ni is not. The other metal elements correspond to the metal elements represented by the co-deposited ions in this invention.
[0044] The lanthanide-poor intermetallic compound may be Al4Eu, Al3Nd, or Zn. 17 Sm2, Ga2Eu, Ge 16 La, Si2Nd, Pb3Nd, Sn3Ce, In3Gd, Mn 23 Nd6, Ni5Pr, Co 17 Sm2, EuCd6, Fe 17 Ce2 and Zn 11 One or more of Nd.
[0045] In some preferred embodiments of the present invention, when the lanthanide element is Eu, the co-deposited ion is Al(III), Ga(III), or Cd(II).
[0046] In some preferred embodiments of the present invention, when the lanthanide element is Sm, the co-deposited ion is Zn(II) or Co(II).
[0047] In some preferred embodiments of the present invention, when the lanthanide element is La, the co-deposited ion is Ge(IV).
[0048] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Al(III), Si(IV), Pb(II), Mn(II) or Zn(II).
[0049] In some preferred embodiments of the present invention, when the lanthanide element is Ce, the co-deposited ion is Sn(II) or Fe(II).
[0050] In some preferred embodiments of the present invention, when the lanthanide element is Gd, the co-deposited ion is In(II).
[0051] In some preferred embodiments of the present invention, when the lanthanide element is Pr, the co-deposited ion is Ni(II).
[0052] In this invention, the working electrode is the substrate material for co-deposition, and it has a significant impact on the occurrence of co-deposition. Not every substrate material is suitable for every lanthanide co-deposition system; a suitable substrate material needs to be selected for a specific co-deposition system. The mechanism by which the substrate material affects the success of co-deposition is complex, involving tensile and compressive stresses caused by the mismatch in thermal expansion between the material and the deposit. Inappropriate selection may lead to co-deposition failure. Furthermore, alloying effects may exist between the substrate material and the co-deposition alloy, affecting the co-deposition effect.
[0053] In some preferred embodiments of the present invention, when the lanthanide element is Eu, the working electrode is made of Ni, Pt, or Mo.
[0054] In some preferred embodiments of the present invention, when the lanthanide element is Sm, the working electrode is made of Mo or Cu material.
[0055] In some preferred embodiments of the present invention, when the lanthanide element is La, the working electrode is made of Cu material.
[0056] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the working electrode is a Pt, Ir, Mo, Cu or Cu-Zn alloy material.
[0057] In some preferred embodiments of the present invention, when the lanthanide element is Ce, the working electrode is a Pd or Cu material.
[0058] In some preferred embodiments of the present invention, when the lanthanide element is Gd, the working electrode is made of Mo material.
[0059] In some preferred embodiments of the present invention, when the lanthanide element is Pr, the working electrode is made of C material.
[0060] In this invention, preferably, the constant potential of the constant potential electrolysis needs to be selected within a specific potential range for a specific system.
[0061] In some preferred embodiments of the present invention, when the lanthanide element is Eu, the co-deposited ion is Al(III), and the working electrode is Ni material, the constant potential is 0.18V.
[0062] In some preferred embodiments of the present invention, when the lanthanide element is Eu, the co-deposited ion is Ga(III), and the working electrode is Pt material, the constant potential is 0.24V.
[0063] In some preferred embodiments of the present invention, when the lanthanide element is Eu, the co-deposited ion is Cd(II), and the working electrode is Mo material, the constant potential is 0.30V.
[0064] In some preferred embodiments of the present invention, when the lanthanide element is Sm, the co-deposited ion is Zn(II), and the working electrode is Mo material, the constant potential is 0.38V.
[0065] In some preferred embodiments of the present invention, when the lanthanide element is Sm, the co-deposited ion is Co(II), and the working electrode is Cu material, the constant potential is 0.22V.
[0066] In some preferred embodiments of the present invention, when the lanthanide element is La, the co-deposited ion is Ge(IV), and the working electrode is Cu material, the constant potential is 0.42V.
[0067] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Al(III), and the working electrode is a Cu-Zn alloy, the constant potential is 0.18V.
[0068] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Si(IV), and the working electrode is Pt material, the constant potential is 0.40V.
[0069] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Pb(II), and the working electrode is Ir material, the constant potential is 0.42V.
[0070] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Mn(II), and the working electrode is Cu material, the constant potential is 0.35V.
[0071] In some preferred embodiments of the present invention, when the lanthanide element is Nd, the co-deposited ion is Zn(II), and the working electrode is Mo material, the constant potential is 0.55V.
[0072] In some preferred embodiments of the present invention, when the lanthanide element is Ce, the co-deposited ion is Sn(II), and the working electrode is Pd material, the constant potential is 0.33V.
[0073] In some preferred embodiments of the present invention, when the lanthanide element is Ce, the co-deposited ion is Fe(II), and the working electrode is Cu material, the constant potential is 0.23V.
[0074] In some preferred embodiments of the present invention, when the lanthanide element is Gd, the co-deposited ion is In(II), and the working electrode is Mo material, the constant potential is 0.33V.
[0075] In some preferred embodiments of the present invention, when the lanthanide element is Pr, the co-deposited ion is Ni(II), and the working electrode is C material, the constant potential is 0.21V.
[0076] Because Be has a high reduction potential, the electrochemical window of the beryllium salt system is narrow. Most redox electrochemical signals of lanthanides are outside this window and cannot be observed, hence the limited number of researchers studying them. However, the method for separating lanthanides from the beryllium salt system in this invention is a precedent for using co-deposition technology to separate lanthanides from the beryllium salt system.
[0077] In this invention, to achieve co-deposition of lanthanides without Be deposition, it is necessary to select suitable co-deposition ions and deposition potentials, which is not an easy task. The co-deposition of lanthanides and the aforementioned co-deposition ions in a beryllium salt system cannot be simply deduced from common knowledge in the field, but was discovered accidentally by the inventors through extensive experimental screening. According to "Modern Alloy Electrodeposition Theory and Technology" (ISBN: 9787118107630) published by the National Defense Industry Press, the basic condition for alloy electrodeposition is that the deposition potentials of the two metals must be very close or equal. Only in this way can alloy electrodeposition, i.e., metal co-deposition, occur. The deposition potential of lanthanides relative to Be(II) / Be is below -0.5V, while the deposition potential of the co-deposition ions involved in this invention is above +0.2V relative to Be(II) / Be, and some even exceed 0.5V. Therefore, in the co-deposition system of this invention, the deposition potentials of beryllium and the co-deposition ions differ by more than 0.7, significantly different from conventional co-deposition problems.
[0078] The reagents and raw materials used in this invention are all commercially available.
[0079] The positive and progressive effects of this invention are as follows:
[0080] This invention employs constant-potential electrolysis of beryllium salt systems containing lanthanides using specific co-deposition ions. This allows the lanthanides to co-deposit along with the co-deposition ions, while avoiding the deposition of large amounts of beryllium or other metallic elements (such as U, Th, and Zr), thus achieving the separation of lanthanide fission products. Compared to fuel remodeling methods, this invention can directly remove lanthanide fission products from molten salt reactor fuel salts. It has low equipment requirements, simple operation, high separation efficiency, and low cost, significantly improving the processing efficiency of molten salt reactor fuels and the economics of the reactor. Attached Figure Description
[0081] Figure 1 This is a schematic diagram of the structure of a beryllium reference electrode.
[0082] Figure 2 The image shows the XRD pattern of the co-deposition product obtained in Example 2.
[0083] Explanation of reference numerals in the attached figures:
[0084] 1. Beryllium rod, 2. Inert material sleeve, 3. Li-BeF2 molten salt. Detailed Implementation
[0085] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0086] In the embodiments and comparative examples of the present invention, the electrochemical workstations used are all CS350M KOSTER electrochemical workstations.
[0087] In the embodiments and comparative examples of this invention, the reference electrodes used are all beryllium electrodes of the same specification. A schematic diagram of the beryllium electrode structure is shown below. Figure 1 As shown, the beryllium rod has a diameter of 2 mm, the alumina sleeve has a wall thickness of 2 mm, the thinnest part at the bottom of the tube has a thickness of 0.5 mm, and the total volume of the liquid LiF-BeF2 molten salt accounts for 0.4% of the volume of the boron nitride tube.
[0088] (1) Method for measuring the concentration of lanthanides in molten salt using ICP-AES:
[0089] Quantitatively weigh 0.2000 g of molten salt sample, digest it with 20% concentrated nitric acid solution, and then fractionally dilute it 10,000 times with 1% dilute nitric acid solution for ICP-AES determination. The working curve for quantitative analysis was prepared using standard lanthanide element solutions with sequential concentrations of 0.01, 0.03, 0.05, 0.1, and 0.5 μg / mL. Other conditions were selected according to the instrument's instruction manual. The ICP-AES instrument manufacturer was PerkinElmer (USA), and the instrument model was Optima 8000.
[0090] (2) Method for XRD analysis of co-deposited products: After electrolysis, the electrodeposited metal sheet is removed, the molten salt attached to the electrode surface is removed, and the deposits on the electrode sheet surface are analyzed by an XRD analyzer. The XRD analyzer manufacturer is Malvern Panaco, and the XRD analyzer model is X-Pert Powder. After obtaining the spectrum, it is compared with the standard PDF card to determine the crystal structure information of the deposits.
[0091] Example 1
[0092] Eu-Al co-deposition separation of Eu in the LiF-BeF2-EuF3-AlF3 molten salt system.
[0093] Weigh out 51g LiF, 46g BeF2, 1g EuF3 and 2g AlF3 respectively, mix them evenly and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 500℃ under an argon atmosphere for later use.
[0094] A Ni metal sheet is used as the working electrode, a platinum metal sheet as the auxiliary electrode, and a beryllium electrode as the reference electrode. The working electrode and the auxiliary electrode form a conductive circuit, and constant potential electrolysis is performed under the control of an electrochemical workstation. The Ni electrode has a specification of 7mm×20mm×1mm, and the platinum electrode has a specification of 10mm×30mm×1mm.
[0095] Electrolysis at a constant potential of 0.18V for 2 hours resulted in a 46.2% decrease in the Eu concentration in the molten salt, as measured by ICP-AES (indicating that 46.2% of the Eu content in 1g EuF3 was precipitated). Al-Eu co-deposition products were obtained on the electrode. XRD analysis showed that the co-deposition products mainly existed in the form of Al4Eu, which is a lanthanide-poor intermetallic compound. Eu was thus enriched and separated on the electrode.
[0096] Example 2
[0097] Co-deposition separation of Nd in the LiF-BeF2-NdF3-AlF3 molten salt system.
[0098] Weigh out 25g LiF, 46g BeF2, 1g NdF3 and 2g AlF3 respectively, mix them evenly and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 600℃ under an argon atmosphere for later use.
[0099] Using a brass metal sheet as the working electrode, glassy carbon as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The brass electrode dimensions were 7mm × 20mm × 1mm, and the glassy carbon electrode dimensions were 10mm × 30mm × 3mm.
[0100] Electrolysis at a constant potential of 0.18V for 2 hours resulted in a 36.5% decrease in the Nd concentration in the molten salt, as measured by ICP-AES (indicating that 36.5% of the Nd content in 1g of NdF3 was precipitated). Nd-Al co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Al3Nd. This co-deposited product is a lanthanide-poor intermetallic compound. The XRD pattern is shown below. Figure 2 As shown, Nd can be enriched and separated on the electrode.
[0101] Example 3
[0102] Co-deposition separation of Sm in the LiF-BeF2-SmF3-ZnF2 molten salt system.
[0103] Weigh out 25g LiF, 46g BeF2, 1g SmF3, and 2g ZnF2 respectively, mix them evenly, and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 600℃ under an argon atmosphere for later use.
[0104] Using a Mo metal sheet as the working electrode, glassy carbon as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Mo electrode dimensions were 7mm × 20mm × 1mm, and the glassy carbon electrode dimensions were 10mm × 30mm × 3mm.
[0105] Electrolysis at a constant potential of 0.38V for 2 hours resulted in a 43.7% decrease in the Sm concentration in the molten salt, as measured by ICP-AES (indicating that 43.7% of the Sm content in 1g SmF3 was precipitated). Zn-Sm co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Zn. 17 Sm exists in the form of Sm2, and the co-deposition product is a lanthanide-poor intermetallic compound. Sm can be enriched and separated on the electrode.
[0106] Example 4
[0107] Co-deposition separation of Eu in the LiF-BeF2-UF4-EuF3-GaF3 molten salt system.
[0108] Weigh out 76g LiF, 46g BeF2, 2g UF4, 1g EuF3, and 3g GaF3 respectively, mix them evenly, and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 600℃ under an argon atmosphere for later use.
[0109] Using a Pt metal sheet as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Pt electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0110] Electrolysis at a constant potential of 0.24V for 2 hours resulted in a 38.1% decrease in the concentration of Eu in the molten salt, as measured by ICP-AES (indicating that 38.1% of Eu was precipitated from 1g of EuF3). Ga-Eu co-deposition products were obtained on the electrode. XRD analysis showed that the co-deposition products mainly existed in the form of Ga2Eu, which is a lanthanide-poor intermetallic compound. Eu was thus enriched and separated on the electrode.
[0111] Example 5
[0112] Co-deposition separation of La in the LiF-BeF2-ThF4-LaF3-GeF4 molten salt system.
[0113] Weigh out 48g LiF, 46g BeF2, 2g ThF4, 1g LaF3, and 3g Li2GeF6 respectively, mix them evenly, and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 600℃ under an argon atmosphere for later use.
[0114] Using a Cu metal sheet as the working electrode, glassy carbon as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Cu electrode dimensions were 7mm × 20mm × 1mm, and the glassy carbon electrode dimensions were 10mm × 30mm × 3mm.
[0115] Electrolysis at a constant potential of 0.42V for 2 hours resulted in a 35.5% decrease in the concentration of La in the molten salt, as measured by ICP-AES (indicating that 35.5% of the La content in 1g of LaF3 was precipitated). Ge-La co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Ge. 16 La exists in the form of lanthanides, and the co-deposition product is a lanthanide-poor intermetallic compound. La can be enriched and separated on the electrode.
[0116] Example 6
[0117] Co-deposition separation of Nd in the LiF-BeF2-UF4-ThF4-NdF3-SiF4 molten salt system.
[0118] Weigh out 104g LiF, 47g BeF2, 2g UF4, 2g ThF4, 1g NdF3, and 4g Li2SiF6 respectively, mix them evenly, and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 700℃ under a helium atmosphere for later use.
[0119] Using a Pt metal sheet as the working electrode, a nickel metal sheet as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Pt electrode dimensions were 7mm × 20mm × 1mm, and the nickel auxiliary electrode dimensions were 10mm × 30mm × 3mm.
[0120] Electrolysis at a constant potential of 0.40 V for 2 hours resulted in a 35.5% decrease in the Nd concentration in the molten salt, as measured by ICP-AES (indicating that 35.5% of the Nd content in 1g of NdF3 was precipitated). Si-Nd co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Si2Nd, which is a lanthanide-poor intermetallic compound. Nd was thus enriched and separated on the electrode.
[0121] Example 7
[0122] Co-deposition separation of Nd in the LiF-BeF2-UF4-ThF4-ZrF4-NdF3-PbF2 molten salt system.
[0123] 104g LiF, 47g BeF2, 2g UF4, 2g ThF4, 5g ZrF4, 1g NdF3, and 3g PbF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 800℃ under a helium atmosphere. Using an Ir metal sheet as the working electrode, a nickel metal sheet as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Ir electrode dimensions were 7mm × 20mm × 1mm, and the nickel auxiliary electrode dimensions were 10mm × 30mm × 3mm.
[0124] Electrolysis at a constant potential of 0.42V for 2 hours resulted in a 33.1% decrease in the Nd concentration in the molten salt, as measured by ICP-AES (indicating that 33.1% of Nd was precipitated from 1g of NdF3). Pb-Nd co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Pb3Nd, which is a lanthanide-poor intermetallic compound. Nd was thus enriched and separated on the electrode.
[0125] Example 8
[0126] Co-deposition separation of Ce in the LiF-BeF2-CeF3-SnF2 molten salt system.
[0127] 51g LiF, 46g BeF2, 1g CeF3, and 2g SnF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 700℃ under an argon atmosphere. A constant potential electrolysis was performed using a Pd metal sheet as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Pd electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0128] Electrolysis at a constant potential of 0.33V for 2 hours resulted in a 37.8% decrease in Ce concentration in the molten salt, as measured by ICP-AES (indicating that 37.8% of Ce content precipitated from 1g of CeF3). Sn-Ce co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Sn3Ce, which is a lanthanide-poor intermetallic compound. Ce was thus enriched and separated on the electrode.
[0129] Example 9
[0130] Co-deposition separation of Gd in the LiF-BeF2-UF4-GdF3-InF2 molten salt system.
[0131] 78g LiF, 47g BeF2, 2g UF4, 1g GdF3, and 2g InF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 650℃ under an argon atmosphere. A constant potential electrolysis was performed using a Mo metal sheet as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Mo electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0132] Electrolysis at a constant potential of 0.33V for 3 hours resulted in a 43.5% decrease in Gd concentration in the molten salt, as measured by ICP-AES (indicating that 43.5% of the Gd content in 1g GdF3 was precipitated). In-Gd co-deposition products were obtained on the electrode. XRD analysis showed that the co-deposition products mainly existed in the form of In3Gd, which is a lanthanide-poor intermetallic compound. Gd was thus enriched and separated on the electrode.
[0133] Example 10
[0134] Co-deposition separation of Nd in the LiF-BeF2-ThF4-NdF3-MnF2 molten salt system.
[0135] 52g LiF, 47g BeF2, 2g ThF4, 1g NdF3, and 2g MnF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 600℃ under an argon atmosphere. A constant potential electrolysis was performed using a Cu metal sheet as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Cu electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0136] Electrolysis at a constant potential of 0.35V for 3 hours resulted in a 42.7% decrease in Nd concentration in the molten salt, as measured by ICP-AES (indicating that 42.7% of Nd content precipitates out of 1g NdF3). Mn-Nd co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Mn. 23 The Nd6 form exists, and the co-deposition product is a lanthanide-poor intermetallic compound. Nd can be enriched and separated on the electrode.
[0137] Example 11
[0138] Co-deposition separation of Pr in the LiF-BeF2-PrF3-NiF2 molten salt system.
[0139] 52g LiF, 47g BeF2, 1g PrF3, and 2g NiF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 650℃ under an argon atmosphere. A constant potential electrolysis was performed using a C-plate as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The C-plate electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0140] Electrolysis at a constant potential of 0.21V for 3 hours resulted in a 21.2% decrease in the concentration of Pr in the molten salt, as measured by ICP-AES (indicating that 21.2% of Pr was precipitated from 1g of PrF3). Ni-Pr co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Ni5Pr, which is a lanthanide-poor intermetallic compound. Pr was thus enriched and separated on the electrode.
[0141] Example 12
[0142] Co-deposition separation of Sm in the LiF-BeF2-SmF3-CoF2 molten salt system.
[0143] 52g of LiF, 47g of BeF2, 1g of SmF3, and 2g of CoF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 500℃ under an argon atmosphere. A constant potential electrolysis was performed using a Cu metal sheet as the working electrode, glassy carbon as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Cu electrode dimensions were 7mm × 20mm × 1mm, and the glassy carbon electrode dimensions were 10mm × 30mm × 3mm.
[0144] Electrolysis at a constant potential of 0.22V for 3 hours resulted in a 24.5% decrease in the Sm concentration in the molten salt, as measured by ICP-AES (indicating that 24.5% of the Sm content in 1g of SmF3 was precipitated). Co-Sm co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Co. 17 Sm exists in the form of Sm2, and the co-deposition product is a lanthanide-poor intermetallic compound. Sm can be enriched and separated on the electrode.
[0145] Example 13
[0146] Co-deposition separation of Ce in the LiF-BeF2-CeF3-FeF2 molten salt system.
[0147] 26g LiF, 47g BeF2, 1g CeF3, and 2g FeF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 600℃ under an argon atmosphere. Constant potential electrolysis was performed using a Cu metal sheet as the working electrode, a nickel electrode as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Cu working electrode dimensions were 10mm × 30mm × 3mm, and the nickel electrode dimensions were 10mm × 40mm × 2mm.
[0148] Electrolysis at a constant potential of 0.23V for 3 hours resulted in a 25.4% decrease in Ce concentration in the molten salt, as measured by ICP-AES (indicating that 25.4% of Ce content precipitates out of 1g CeF3). Ce-Fe co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Fe. 17 Ce exists in the form of Ce2, and this co-deposition product is a lanthanide-poor intermetallic compound. Ce can be enriched and separated on the electrode.
[0149] Example 14
[0150] Co-deposition separation of Eu in the LiF-BeF2-EuF3-CdF2 molten salt system.
[0151] 26g LiF, 47g BeF2, 1g EuF3, and 2g CdF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 600℃ under an argon atmosphere. A constant potential electrolysis was performed using a Mo metal sheet as the working electrode, a nickel electrode as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Mo working electrode dimensions were 10mm × 30mm × 3mm, and the nickel electrode dimensions were 10mm × 40mm × 2mm.
[0152] Electrolysis at a constant potential of 0.30 V for 3 h resulted in a 31.3% decrease in the Eu concentration in the molten salt, as measured by ICP-AES (indicating that 31.3% of Eu was precipitated from 1 g of EuF3). Eu-Cd co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products mainly existed in the form of Cd6Eu, which is a lanthanide-poor intermetallic compound. Eu was thus enriched and separated on the electrode.
[0153] Example 15
[0154] Co-deposition separation of Nd in the LiF-BeF2-ThF4-NdF3-ZnF2 molten salt system.
[0155] 52g LiF, 47g BeF2, 2g ThF4, 1g NdF3, and 2g ZnF2 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 550℃ under an argon atmosphere. A constant potential electrolysis was performed using a Mo metal sheet as the working electrode, graphite as the auxiliary electrode, and a beryllium electrode as the reference electrode, under the control of an electrochemical workstation. The Mo electrode dimensions were 7mm × 20mm × 1mm, and the graphite electrode dimensions were 10mm × 30mm × 3mm.
[0156] Electrolysis at a constant potential of 0.55V for 3 hours resulted in a 41.6% decrease in the Nd concentration in the molten salt, as measured by ICP-AES (indicating that 41.6% of the Nd content in 1g of NdF3 was precipitated). Nd-Zn co-deposited products were obtained on the electrode. XRD analysis showed that the co-deposited products were mainly composed of Zn. 11 The Nd form exists, and the co-deposition product is a lanthanide-poor intermetallic compound. Nd can be enriched and separated on the electrode.
[0157] Comparative Example 1
[0158] Electrolytic separation of Eu in the LiF-BeF2-EuF3 molten salt system.
[0159] 26g LiF, 47g BeF2, and 1g EuF3 were weighed out, mixed thoroughly, and placed in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. The mixture was then melted at 600℃ under an argon atmosphere. Using a Ni metal sheet as the working electrode, glassy carbon as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Ni electrode dimensions were 7mm × 20mm × 1mm, and the glassy carbon electrode dimensions were 10mm × 30mm × 3mm.
[0160] The electrolysis conditions were: potential 0.2V. After 2 hours of electrolytic deposition, the Eu concentration in the molten salt did not decrease significantly. XRD analysis showed that the deposits on Ni were mainly NiBe. The main reason for the failure of Eu electrolytic extraction separation was the lack of addition of co-deposited ions, such as Al. 3+ .
[0161] Comparative Example 2
[0162] Electrolytic separation of Nd in the LiF-BeF2-UF4-ThF4-NdF3 molten salt system.
[0163] Weigh out 104g LiF, 47g BeF2, 2g UF4, 2g ThF4 and 1g NdF3 respectively, mix them evenly and place them in a glassy carbon crucible with an inner diameter of 40mm and a height of 60mm. Melt the crucible at 600℃ under a helium atmosphere for later use.
[0164] Using an Au metal sheet as the working electrode, a nickel metal sheet as the auxiliary electrode, and a beryllium electrode as the reference electrode, constant potential electrolysis was performed under the control of an electrochemical workstation. The Au electrode dimensions were 7mm × 20mm × 1mm, and the nickel auxiliary electrode dimensions were 10mm × 30mm × 3mm.
[0165] The electrolysis conditions were: constant potential of 0.45V. After 2 hours of electrolytic deposition, the Nd concentration in the molten salt did not decrease significantly. The main reason for the failure of Nd electrolytic extraction separation was the unsuitable selection of electrode materials and the lack of added co-deposited ions. The formation of low-melting-point beryllium-rich Au-Be intermetallic compounds on the Au electrode led to Au dissolution and loss.
Claims
1. A method for separating lanthanide elements in a beryllium salt system, characterized in that: The method comprises the following steps: subjecting a beryllium salt system containing a lanthanide element and co-deposited ions to constant potential electrolysis; Wherein, the beryllium salt system includes beryllium fluoride salt; Wherein, the constant potential of the constant potential electrolysis is 0.18~0.55V; The constant potential electrolysis causes the lanthanide element and the co-deposited ions to co-deposit on the working electrode and form a lanthanide-poor intermetallic compound to precipitate; The lanthanide element is Eu, and the co-deposited ions are Al(III), Ga(III) or Cd(II); Or, the lanthanide element is Sm, and the co-deposited ion is Zn(II); Or, the lanthanide element is La, and the co-deposited ion is Ge(IV); Or, the lanthanide element is Nd, and the co-deposited ion is Al(III), Si(IV), Pb(II), Mn(II) or Zn(II); Or, the lanthanide element is Ce, and the co-deposited ion is Sn(II); Alternatively, the lanthanide element is Gd, and the co-deposited ion is In(II).
2. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium fluoride salt is one or more of FLiBe, FNaBe and BeF2; And / or, the beryllium salt system further includes other fluoride salts except the beryllium fluoride salt.
3. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium salt system also includes one or more of LiF, NaF, UF4, ThF4 and ZrF4.
4. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium salt system includes BeF2 and LiF; Or, the beryllium salt system includes BeF2 and NaF; Or, the beryllium salt system includes LiF, BeF2 and UF4; Or, the beryllium salt system includes LiF, BeF2 and ThF4; Or, the beryllium salt system includes LiF, BeF2, UF4 and ThF4; Alternatively, the beryllium salt system includes LiF, BeF2, UF4, ThF4 and ZrF4.
5. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium salt system includes 67LiF-33BeF2.
6. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium salt system includes 57NaF-43BeF2.
7. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The lanthanide element is present in the form of lanthanide fluoride; And / or, the lanthanide element is derived from lanthanide fission products.
8. The method for separating lanthanide elements in a beryllium salt system according to claim 7, characterized in that: The lanthanide fluoride is one or more of NdF3, GdF3, CeF3, LaF3, SmF3 and EuF3.
9. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The beryllium salt system is heated and melted before constant potential electrolysis; And / or, the atmosphere in which the constant potential electrolysis is performed is an inert gas atmosphere; And / or, the power source for constant potential electrolysis is a constant potential electrolysis power source or a constant potential instrument with a potential control function; And / or, the constant potential electrolysis is performed under the control of an electrochemical workstation; And / or, the constant potential of the constant potential electrolysis is 0.3V~0.5V.
10. The method for separating lanthanide elements in a beryllium salt system according to claim 9, characterized in that: The heating and melting temperature is 500-800°C.
11. The method for separating lanthanide elements in a beryllium salt system according to claim 9, characterized in that: The heating and melting is performed under an inert gas atmosphere.
12. The method for separating lanthanide elements in a beryllium salt system according to claim 11, characterized in that: The inert gas is argon or helium.
13. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The atmosphere of the constant potential electrolysis is an inert gas atmosphere, and the inert gas is argon or helium.
14. The method for separating lanthanide elements in a beryllium salt system according to claim 9, characterized in that: The electrochemical workstation is a Coster electrochemical workstation.
15. The method for separating lanthanide elements in a beryllium salt system according to claim 14, characterized in that: The electrochemical workstation is a CS350M Cost electrochemical workstation.
16. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The lanthanum-poor intermetallic compound is Al4Eu, Al3Nd, Zn 17 Sm2, Ga2Eu, Ge 16 La, Si2Nd, Pb3Nd, Sn3Ce, In3Gd, Mn 23 Nd6, EuCd6 and Zn 11 One or more of Nd.
17. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The constant potential electrolysis is performed using a three-electrode system, which includes a working electrode, an auxiliary electrode and a reference electrode.
18. The method for separating lanthanide elements in a beryllium salt system according to claim 17, characterized in that: The working electrode is made of Ni, Cu, Cu-Zn alloy, Mo, Pd, Ir, Pt or C material; and / or, the purity of the electrode material of the working electrode is not less than 95%; And / or, the auxiliary electrode is graphite, glassy carbon, Pt, Mo or Ni; And / or, the purity of the electrode material of the auxiliary electrode is not less than 95%.
19. The method for separating lanthanide elements in a beryllium salt system according to claim 17, characterized in that: The reference electrode is a beryllium electrode; And / or, the purity of the electrode material of the reference electrode is not less than 95%.
20. The method for separating lanthanide elements in a beryllium salt system according to claim 19, characterized in that: The beryllium electrode comprises a beryllium metal rod, LiF-BeF2 molten salt and a casing.
21. The method for separating lanthanide elements in a beryllium salt system according to claim 20, characterized in that: The diameter of the beryllium metal rod is 2-3 mm; And / or, the molar ratio of LiF to BeF2 in the LiF-BeF2 molten salt is 1:1 to 4:1; And / or, the ratio of the total volume of the LiF-BeF2 molten salt to the volume of the sleeve is 0.3-0.5; And / or, the wall thickness of the sleeve is 1-5 mm; And / or, the material of the casing is an inert material resistant to molten salt corrosion; And / or, the thickness of the thinnest part of the bottom of the sleeve is 0.1-1.0 mm.
22. The method for separating lanthanide elements in a beryllium salt system according to claim 21, characterized in that: The molar ratio of LiF to BeF2 in the LiF-BeF2 molten salt is 2:
1.
23. The method for separating lanthanide elements in a beryllium salt system according to claim 21, characterized in that: The sleeve is made of ceramic material.
24. The method for separating lanthanide elements in a beryllium salt system according to claim 23, characterized in that: The material of the sleeve is hot-pressed boron nitride, aluminum oxide, magnesium oxide or zirconium oxide.
25. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The lanthanide element is Eu, and the working electrode is Ni, Pt or Mo material; Or, the lanthanide element is Sm, and the working electrode is Mo or Cu material; Or, the lanthanide element is La, and the working electrode is Cu material; Or, the lanthanide element is Nd, and the working electrode is Pt, Ir, Mo, Cu or Cu-Zn alloy material; Or, the lanthanide element is Ce, and the working electrode is Pd or Cu material; Alternatively, the lanthanide element is Gd, and the working electrode is Mo material.
26. The method for separating lanthanide elements in a beryllium salt system according to claim 1, characterized in that: The lanthanide element is Eu, the co-deposited ion is Al(III), the working electrode is Ni material, and the constant potential is 0.18V; Or, the lanthanide element is Eu, the co-deposited ion is Ga(III), the working electrode is Pt material, and the constant potential is 0.24V; Or, the lanthanide element is Eu, the co-deposited ion is Cd(II), the working electrode is Mo material, and the constant potential is 0.30 V; Or, the lanthanide element is Sm, the co-deposited ion is Zn(II), the working electrode is Mo material, and the constant potential is 0.38V; Or, the lanthanide element is La, the co-deposited ion is Ge(IV), the working electrode is Cu material, and the constant potential is 0.42V; Or, the lanthanide element is Nd, the co-deposited ion is Al(III), the working electrode is a Cu-Zn alloy, and the constant potential is 0.18 V; Or, the lanthanide element is Nd, the co-deposited ion is Si(IV), the working electrode is a Pt material, and the constant potential is 0.40 V; Or, the lanthanide element is Nd, the co-deposited ion is Pb(II), the working electrode is Ir material, and the constant potential is 0.42V; Or, the lanthanide element is Nd, the co-deposited ion is Mn(II), the working electrode is Cu material, and the constant potential is 0.35V; Or, the lanthanide element is Nd, the co-deposited ion is Zn(II), the working electrode is Mo material, and the constant potential is 0.55V; Or, the lanthanide element is Ce, the co-deposited ion is Sn(II), the working electrode is Pd material, and the constant potential is 0.33V; Or, the lanthanide element is Gd, the co-deposited ion is In(II), the working electrode is Mo material, and the constant potential is 0.33V.
Citation Information
Patent Citations
Separation method of fluorine lithium beryllium molten salt system rare earth fission product
CN117831817A